2015
DOI: 10.1063/1.4907603
|View full text |Cite
|
Sign up to set email alerts
|

Squeeze strengthening of magnetorheological fluids using mixed mode operation

Abstract: Elastic percolation transition in nanowire-based magnetorheological fluids Appl. Phys. Lett. 95, 014102 (2009); 10.1063/1.3167815 Dynamic yield stress enhancement in bidisperse magnetorheological fluids J. Rheol. 49, 1521 (2005); 10.1122/1.2085175Study on the mechanism of the squeeze-strengthen effect in magnetorheological fluids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…15) when a force of approximately 30 N obtained at 0 A is increased to 122 N, 160 N, and 240 N under 1.4 A excitation for the squeeze, shear-flow, and mixed modes, respectively. Again, this fluid performance enhancement under mixed mode operation is in agreement with those reported by Sarkar and Hirani [27], Spaggiari and Dragoni [28] and Becnel et al [29] although the shearing of the fluid in their mixed squeeze-shear cells was achieved through piston rotations rather than through a direct axial motion which is realized in this investigation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…15) when a force of approximately 30 N obtained at 0 A is increased to 122 N, 160 N, and 240 N under 1.4 A excitation for the squeeze, shear-flow, and mixed modes, respectively. Again, this fluid performance enhancement under mixed mode operation is in agreement with those reported by Sarkar and Hirani [27], Spaggiari and Dragoni [28] and Becnel et al [29] although the shearing of the fluid in their mixed squeeze-shear cells was achieved through piston rotations rather than through a direct axial motion which is realized in this investigation.…”
Section: Resultssupporting
confidence: 93%
“…Again, this fluid performance enhancement under mixed mode operation is in agreement with those reported by Sarkar and Hirani, 27 Spaggiari and Dragoni 28 and Becnel et al. 29 although the shearing of the fluid in their mixed squeeze-shear cells was achieved through piston rotations rather than through a direct axial motion which is realised in this investigation.
Figure 12.Variation of transmitted force with time for single and mixed modes under oscillatory motion.
Figure 13.Variation of transmitted force with displacement for single and mixed modes under oscillatory motion.
Figure 14.Variation of transmitted force with velocity for single and mixed modes under oscillatory motion.
Figure 15.Variation of yield force with current for MR fluid under single and mixed modes.
…”
Section: Resultssupporting
confidence: 92%
“…In another study, Spaggiari and Dragoni (2014) demonstrated that the yield stress of MRF-130CG of Lord Corp. was increased by 200% as the pressure was increased to 30 bar at the highest magnetic field of 300 mT in shear mode. Becnel et al (2015) also showed that the yield stress of MRF-132DG of Lord Corp. was increased by 77% for a rotary MR energy absorber. Squeeze strengthening effects were realized when the magnetic field intensity exceeded 50 kA/m.…”
Section: Comparisons Between Theoretical and Experimental Resultsmentioning
confidence: 89%
“…The axial activation length is only the portion of the rotor where the flux lines concatenate and is two time LP= 6 mm, while the total axial length of the rotor surrounded by the MR fluid is L=24mm. The shear stress value τ, acting on the stator wall can be directly linked to the torque measured by the sensor as follows [22,29,30] = 2 ( + ℎ) 2…”
Section: Searle Magnetorheometermentioning
confidence: 99%